Efficient Deoxygenation of Palm Oil to Green Diesel Using a Metal Oxide Catalysts Supported on ZrO2-Enhanced Graphene Oxide - Attared Fadhil Hassan; Hassan Thamer Abdulsahib; Faris Abdulridha Jassim Al-Doghachi; Taufiq-Yap Yun Hin (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
NiO, Fe2O3, and bimetallic oxide NiFe2O4 catalysts supported on graphene oxide and promoted with ZrO2 were synthesized via wet-impregnation approach. A systematic characterization of the catalysts physicochemical properties was evaluated using X-ray diffraction (XRD), Thermogravimetric analysis (TGA), Fourier Transform Infrared (FTIR), Temperature -programmed desorption CO2 (TPD-CO2), Brunaur-Emmett-Teller (BET) surface area, Field emission Scanning electron microscopy (FESEM), and Transmission electron microscopy (TEM) analysis. The catalysts were evaluated as heterogeneous catalysts in the deoxygenation (DO) of palm oil for green diesel production under varying operating conditions. Among the catalysts tested, Fe2O3/ZrO2-GO (calcined at 400 °C for 4 h, 5 wt% loading) demonstrated superior catalytic activity, achieving a maximum hydrocarbon yield (HC%) of 98.0%, bio-jet fuel (BJF) selectivity of 40%, and kerosene yield of 86%. The exceptional performance is attributed to the catalyst’s large BET surface area (18.64 m2/g), substantial pore volume (0.027 cm3/g), and moderate surface basicity (3234.65 μmol/g), which collectively facilitate efficient deoxygenation via decarboxylation (DCO2) and decarbonylation (DCO) pathways while suppressing undesired cracking. Furthermore, the catalyst exhibited remarkable stability and reusability over four consecutive reaction cycles, retaining 92% hydrocarbon yield and 80.9% kerosene yield, with BJF selectivity increasing to 84%. The gradual decline in performance is attributed to carbon deposition (coke formation), pore blockage, and sintering-induced degradation of the mesoporous network, as confirmed by post-reaction XRD and BET analysis. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).